SHEIKH YUSUF AL-QARADAWI AND ABDULLAH AN -NA'IM'S PERCEPTION OF ONLINE SALES AGREEMENTS FROM A SHARIA ECONOMIC PERSPECTIVE - Lutfiatun Hasanah; Haqiqotus Sa’adah (IZZI: Jurnal Ekonomi Islam, 2026)
The development of digital technology has given rise to new forms of economic transactions in the form of online buying and selling (e-commerce) , which require examination from the perspective of Islamic law to ensure their continued relevance to sharia principles. This study aims to analyze the perspectives of Shaykh Yusuf al-Qaradawi and Abdullah An-Na‘im regarding online sale and purchase contracts from the viewpoint of sharia economics. The research employs a qualitative method with a literature study (library research) approach, conducted through a critical review of the works of both figures as well as relevant classical and contemporary fiqh literature.The results show that Shaykh Yusuf al-Qaradawi views online buying and selling as a valid form of muamalah as long as it fulfills the pillars and conditions of a contract and is free from elements of riba, gharar, and maysir, while emphasizing the principles of honesty, transparency, and mutual consent between the parties. Meanwhile, Abdullah An-Na‘im stresses the importance of contextualizing and reconstructing Islamic law so that it can respond to contemporary challenges, by making justice and public welfare (maslahah) the primary benchmarks for the validity of transactions. This study finds that although the two scholars employ different methodological approaches, both agree that Islamic legal principles are dynamic and adaptive to the development of digital transactions. These findings are expected to enrich the discourse in sharia economic studies and provide a conceptual foundation for understanding online buying and selling practices that are in line with the maqasid al-shariah in the digital era